UiTM Perak branch empowers multi-agency effort in training tomorrow’s responders for school preparedness program - Azman, Najma (Universiti Teknologi MARA, 2025)
KUALA KANGSAR, 23 May 2025 – In an inspiring effort to build disaster-resilient communities from the ground up, the Disaster Risk Reduction: School Preparedness Program was successfully held at Sekolah Menengah Kebangsaan (SMK) Sayong, Kuala Kangsar, Perak. The program brought together 46 enthusiastic students who participated in a range of engaging and educational activities focused on disaster awareness and emergency preparedness. This meaningful initiative was a result of collaborative volunteerism between Universiti Teknologi MARA Perak Branch; UiTM MERCY Resilient Community Centre (UMRCC), MERCY Malaysia Perak Chapter (MMPC), Think City and Yayasan Khazanah. It brought together a total of 6 volunteers, comprising five lecturers from UiTM Perak Branch, and others are the representatives of MERCY Malaysia and Think City, whose dedication helped ensure the success of the event. The School Preparedness Program is a vital community outreach initiative designed to enhance the disaster response capacity of students, teachers, and the broader school community. The event was carefully structured based on well-developed modules, including group training sessions, educational presentations, and hands-on simulation exercises. These modules aimed to provide participants with practical knowledge and skills, preparing them for potential real-life disaster situations. Through interactive sessions and simulations, students gained firsthand experience on how to react effectively and responsibly during emergencies such as floods, fires, or other natural disasters. This initiative not only nurtures awareness but also cultivates leadership, responsibility, and resilience among young individuals as well as equipping them to become proactive agents of safety in their communities. “It was truly enjoyable, and I’m so proud of the students’ responses; it clearly shows how effective the training and explanation have been. We all had fun, the students are very funny, but they managed to follow along with the modules, so good job!” said Cik Rose Afrina Mansor, who’s the Manager of Climate Resilience, Think City Malaysia. The program stands as a testament to the power of community engagement and inter-agency collaboration in building a safer and more prepared society. With continued efforts like these, it is hoped that more schools and communities will adopt similar preparedness programs to safeguard lives and promote long-term resilience against disasters.